An empirical analysis on sustainable start-up: embedding Environmental, Social and Governance (ESG) into high growth business strategy - Singh, Rashmi; Tarkar, Preeti (Brazilian Journal of Operations & Production Management, 2024)
Goal: The paper aims to explore when, why and how the enterprises can incorporate ESG strategies that will help them in value formation and meeting the expectation of stakeholders. Moreover, with the help of quantitative data, we have analyzed the effect of ESG on high-growth business strategy. Method: A quantitative study was conducted for the test of hypothesis for which the data of 174 respondents was collected with the assistance of a self-administered questionnaire. The information was gathered from the IT companies of different states of India, and for the analysis of data, Correlation and multiple regression was employed with the help of SPSS. Result: The analysis of data has concluded that incorporating ESG from starting itself as a high growth strategy will give a huge boom to the young companies to establish themselves well and have a successful starting. It can be done through starting from the basics, Strengthening the core and Communicating the efforts. All three factors, environment, social, and governance, positively influence the growth strategies of young companies. Moreover, the governance factor was the strongest analyst of growth strategies in young companies, which means that the governance factor greatly influences the growth strategies of young companies. Limitations: The current study is specifically concentrated in India. It is consisted of three variables of ESG where more variables can be included in the scale for increasing the credibility of the scale in the future. Practical implications: The study will help the industries, especially young companies, focus on the ESG concerns as these factors are highly influential for the success and growth of the companies from starting. It has highlighted the easy integration of ESG from starting and embraces the idea of re-evaluating and redefining the strategies and functioning activities to progress and endure profitability. Originality: The study discusses the integration of ESG in young companies from the initial phase of the business, that is, a different from the past studies. Moreover, this is the first study in India concerning the given topic.